125k views
3 votes
Need help please find the inverse of this logarithm function please ❤️ ONLY IF UR GOOD AT MATH!!!!

Need help please find the inverse of this logarithm function please ❤️ ONLY IF UR-example-1

2 Answers

4 votes

as you already know, we start by doing a quick switcheroo on the variables, to get the inverse expression of any expression, so



\bf \textit{Logarithm of exponentials} \\\\ \log_a\left( x^b \right)\implies b\cdot \log_a(x) \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ \stackrel{f(x)}{y}=3\left( 2^(x+3) \right)-4\implies \stackrel{\textit{quick switcheroo}}{x=3\left( 2^(y+3) \right)-4}\implies x+4=3\left( 2^(y+3) \right)



\bf \cfrac{x+4}{3}=2^(y+3)\implies \log\left( \cfrac{x+4}{3} \right)=\log\left( 2^(y+3) \right) \\\\\\ \log\left( \cfrac{x+4}{3} \right)=(y+3)\log\left( 2 \right)\implies \cfrac{\log\left( (x+4)/(3) \right)}{\log(2)}=y+3 \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ ~\hfill \cfrac{\log\left( (x+4)/(3) \right)}{\log(2)}-3=\stackrel{f^(-1)(x)}{y}~\hfill

User Cranio
by
6.3k points
4 votes

Answer:

f-1(x) = log2 [ (x + 4)/3 ] - 3.

Explanation:

Let y = 3(2^(x+3) - 4

3(2^(x + 3) = y + 4

2^(x + 3) = (y + 4)/3

x + 3 = log2 [(y + 4)/3]

x = log2 [ (y + 4)/3 ] - 3

Inverse f-1(x) = log2 [ (x + 4)/3 ] - 3




User Mrhellmann
by
5.8k points